Electronic Audit (E-Audit), Audit Judgement, Corruption Detection and Audit Quality: BPK RI - Luqman Hakim; Raymond Pardomuan; Mitsalina Tantri (Program Studi S3 Ilmu Manajemen, 2023)
Research aims: This research is based on the phenomenon that occurred related to the existence of several limitations faced by the Supreme Audit Agency of the Republic of Indonesia in carrying out audits of financial statements in public sector entities. This condition risks affecting audit quality, resulting in the emergence of information gaps between BPK RI, the public and related stakeholders. The purpose of this study was to examine and analyze whether the effect of each independent variable (X1, X2 and X3), including electronic audit (e-audit), audit judgment and the detection of corruption affecting audit quality as the dependent variable (Y ). Design/Methodology/Approach: The research method used is a quantitative method. This study examines the effect of e-audit, audit judgment and corruption detection on audit quality. This study uses primary and secondary data with a research instrument in the form of a questionnaire. The object of this study is the IB Auditorate as a work unit equivalent to echelon II under the Main Auditorate of State Finance I at the Head Office of the Supreme Audit Agency of the Republic of Indonesia. The number of respondents in this study were 40 auditors/examiners in the IB Auditorate. The type of analysis in this study was statistical descriptive analysis. The statistical analysis tools used are the SPSS and Eviews applications. Research findings: The results of the empirical study revealed that each of the independent variables (X1, X2, and X3), including e-audit, audit judgment and detection of corruption, had a positive and significant effect on audit quality as the dependent variable (Y). Theoretical contribution/Originality: Future research is needed to develop with other indicators besides the quality of electronic audit (e-audit), audit judgement, corruption detection and audit quality.